The evaluation of wastewaters from an oil sand extraction plant - Strosher, M. T.; Peake, E. (1976)
Organic constituents of wastewaters from the existing Athabasca oil sands extraction plant were characterized and quantified. Twenty-one chemical parameters were determined on a total of ten samples taken during November and December, 1975 from the tailings pond dike filter drainage system, the upgrading plant final effluent to the Athabasca River and the intake pond waters. In addition, a number of specific aromatic hydrocarbons and organic sulphur compounds were identified and heavy metals and vanadium were determined. Tailings pond dike filter drainage samples contained 100-120 mg/l of total organic carbon, 69% of which was extractable with organic solvents. Ninety-two percent of the extractable carbon was in the form of oxygenated compounds, including organic acids (79%), phenols (4.5%), ketones (2.7%), aldehydes (1.9%), organic acid esters (1.5%), amides (1.0%), and quinones (0.2%). Organic sulphur compounds averaged 5.3%, organic nitrogen compounds 1.1% and hydrocarbons 0.04% of the extractable material. Upgrading plant effluents contained an average of 36 mg/l of total organic carbon, only 15 mg/l of which was extractable. Oxygenated compounds accounted for 30% of the extractable organic carbon, organic sulphur compounds 17%, nitrogen compounds 7% and hydrocarbons 7%. The remaining 6 mg/l of organic carbon was not accounted for. On the basis of these findings and previously measured water flow data, a calculated daily average of 198 kg (435 lbs) of organic carbon was released to the river from the tailings pond dike filter system and 1460 kg (3,245 lbs) was discharged from the upgrading plant effluent. These amounts corresponded to about 0.8% of the natural organic load of the river. It is recommended that further studies be conducted on these and other wastewaters on a year-round basis to determine (a) the seasonal variations in amounts of organic constituents, (b) the identity of individual compounds, (c) the toxicity of compound groups and, (d) the physical state of existence of the organic compounds. ...